PROSES PENYUSUNAN KOMPOSISI GAMELAN "ARUHARA" - Wahyu Thoyyib Pambayun (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2021)
This article contains the author’s experience in composing gamelan composition, “Aruhara”. In the composing process of “Aruhara”, the author was inspired by the Genderan of Ada-ada Ngobong Dupa presented by Sumiyati. In order to create the gamelan composition “Aruhara”, the author uses reinterpretation approaches. The steps of composing the piece are: observation, exploration, elaboration, rehearsal, and finalization. The process that has been passed has resulted new offers in addressing the gender instrument, such as  the use of patterns, techniques, musical scales and the connection between the instruments. The author hopes this article can be useful as an alternative source to learn gamelan compositions for gamelan composition learners, and it can provides an overview about the discourse, also the performance of Indonesian composers.Keywords::Composition, Gamelan, Gender, Aruhara, Karawitan